2006
DOI: 10.1016/j.bbamem.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways involving the sodium pump stimulate NO production in endothelial cells

Abstract: The cardiac steroid ouabain, a known inhibitor of the sodium pump (Na+, K+ -ATPase), has been shown to release endothelin from endothelial cells when used at concentrations below those that inhibit the pump. The present study addresses the question of which signaling pathways are activated by ouabain in endothelial cells. Our findings indicate that ouabain, applied at low concentrations to human umbilical cord endothelial cells (HUAECs), induces a reaction cascade that leads to translocation of endothelial nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Now, Na, KATPase has been noted as an interesting drug target [Aperia, 2007]. A recent report has shown that, in VECs, suppressing activity of Na, KATPase results in activation of the proliferation and survival pathways and inhibits apoptosis [Orlov et al, 2004;Eva et al, 2006]. Consistent with this report, our results showed that 3BDO inhibited HUVEC apoptosis and maintained their ability in angiogenesis through suppressing Na, K-ATPase activity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Now, Na, KATPase has been noted as an interesting drug target [Aperia, 2007]. A recent report has shown that, in VECs, suppressing activity of Na, KATPase results in activation of the proliferation and survival pathways and inhibits apoptosis [Orlov et al, 2004;Eva et al, 2006]. Consistent with this report, our results showed that 3BDO inhibited HUVEC apoptosis and maintained their ability in angiogenesis through suppressing Na, K-ATPase activity.…”
Section: Discussionsupporting
confidence: 94%
“…A most recent report showed that inhibiting the activity of Na, K-ATPase by ouabain results in activation of the proliferation and survival pathways involving PI3K, Akt activation, stimulation of eNOS (Endothelial Nitric Oxide Synthase), and production of nitric oxide (NO) in human umbilical cord endothelial cells (HUAECs) [Eva et al, 2006]. Not only in vascular endothelial cells, but in VSMCs, inhibition of Na, K-ATPase blocks the development of apoptosis, and also promotes activation of a signaling pathway that blocks apoptosis [Orlov et al, 1999].…”
mentioning
confidence: 99%
“…Unpublished observations from Dr. Alexander Chibalin and coworkers show that A-769662 can inhibit the Na ϩ -K ϩ -ATPase (personal communication). In addition, it has been shown in some (11,21,29,30,50) but not all models (23,24) that inhibition of the Na ϩ -K ϩ -ATPase by ouabain increases PI3-kinase activity, possibly through an association between p85 and the ␣ 1 -subunit of the Na ϩ -K ϩ -ATPase, leading to increased Akt phosphorylation. This effect can be inhibited by wortmannin (30).…”
mentioning
confidence: 99%
“…On the other hand, in cultured rat aortic endothelial cells, ouabain (10 nM) contributes to the bradykinin-stimulated increase of nitric oxide (NO) production by inhibiting plasma membrane Na + ,K + -ATPase activity and increasing intracellular Na + concentration (42). Moreover, Eva et al (43) demonstrated that small quantities of ouabain stimulate NO production in human umbilical artery endothelial cells via PI3K. The binding of ouabain to Na + ,K + -ATPase initiates a signal via PI3K, which turns on the proliferation and survival pathways that involve Akt and that stimulate endogenous nitric oxide synthase (eNOS) and NO production (43).…”
Section: Acute Effects Of Picomole Quantities Of Ouabain On Vascular mentioning
confidence: 99%
“…Moreover, Eva et al (43) demonstrated that small quantities of ouabain stimulate NO production in human umbilical artery endothelial cells via PI3K. The binding of ouabain to Na + ,K + -ATPase initiates a signal via PI3K, which turns on the proliferation and survival pathways that involve Akt and that stimulate endogenous nitric oxide synthase (eNOS) and NO production (43). Because NO is an endothelial factor that activates Na + ,K + -ATPase (44), we speculated that picomole quantities of ouabain could release NO, which, in turn, could stimulate Na + ,K + -ATPase activity, reducing vascular reactivity in normotensive rats.…”
Section: Acute Effects Of Picomole Quantities Of Ouabain On Vascular mentioning
confidence: 99%